Feasibility study on global footwall stability at the Kiirunavaara mine - Nilsson, Mikael (Luleå tekniska universitet, Geoteknologi, 2012)
This feasibility study was carried out over a time period of 6 months by Luleå University of Technology on request by, and in co-operation with, LKAB (Luossavaara Kiirunavaara Aktiebolag).This work reviews the documentation from previous studies including: descriptions of the geomechanical conditions, records of damage and fallouts in the footwall, installed measuring equipment and associated data, modelling attempts of the Kiruna mine as well as scientific publications. from the Chuquicamata, Cadia Hill, Bingham Canyon, Kvannevann, perseverance, Stobie, Ridgeway and Palabora mines. In addition, damage mapping has been carried out in relation to this work and the results are published as separate documents titled “Kartering av huvudnivå 775, 2012, Meddelande 12-20076” and “Kartering av nivåerna 230 – 775 m mellan Y22 – Y28, 2012, Meddelande 12-20077” respectively.The review suggests that the main host rock type in the footwall is a Precambrian aged tracho-andesite locally referred to as syenite porphyry. The syenite porphyry borders the ore and ore contact. The porphyry is replaced by competent granite as one moves westward away from the footwall on levels below 800 m. Documentation of the rock mass at a distance from the ore contact is limited to drift mapping. Information on dominant joint orientations is available for most levels in moderate detail. Dominant joint sets dipping parallel or sub parallel to the orebody are mapped on most levels.The assumed failure mode and mechanisms for the large scale footwall failure have changed as the mine deepened, the prognosis models have been continuously updated to fit observed damage.• 1970s – The outer fracture line was considered traceable using a linear failure surface dipping 50-60˚. (Kiviniemi I ,1977)• 1980s – The dip interval of the failure surface was narrowed to 55-60˚; this model was used into the early 90s. (Finn, 1981),(Dahner, 1990)• 1992 – New failure modes were assumed, the linear model was replaced by circular shear failure through the rock mass with ...